Análise diferencial-estrutural dos municípios de Caucaia e São Gonçalo do Amarante com foco na implantação do complexo industrial - portuário do Pecém - Castro Filho, Francisco de (2009)
This study examines the implementation of the Pecém Industrial and Port Complex, CIPP, as a development strategy of the local area, the municipalities Caucaia and Sao Goncalo do Amarante. From an analysis of shift-share was performed a descriptive analysis of the production structure that allows both the comparison of the structures of the various communes of the CIPP in the state and analyze the industrial and commercial sectors in this region, which are expected to be directly affected with the implementation of the complex. The results indicate that the positive effects found for the growth and regional development can be leveraged in the local economy, for these cities, and this performance can be attributed to the fact of being inserted into the area of influence of the Pecem Industrial and Port area.